Perceptions and experiences of lifestyle interventions in women with polycystic ovary syndrome (PCOS), as a management strategy for symptoms of PCOS - Susan Arentz; Caroline A. Smith; Jason Abbott; Alan Bensoussan (BMC, 2021)
Abstract Background The international clinical practice guidelines for PCOS emphasize diet and exercise as first-line management of clinical signs and symptoms. This study aimed to describe the patterns, perceptions and experiences of lifestyle interventions for women in the community with PCOS. Method An electronic survey of 493 members of two PCOS consumer support groups, collected by cloud-based Survey Monkey, described women's types and patterns of diet and exercise, experiences and perceptions of effectiveness. Women were recruited from the Polycystic Ovary Association of Australia (POSAA) and from the Facebook group, PCOS University Research Group. Associations between participants perceptions of effectiveness, and diet types and exercise patterns were assessed using logistic regression. Response bias for the POSAA group was assessed with a continuum of resistance model. Results 91% of POSAA members and 311 Facebook group members aged 16-50 years responded to the survey. Nearly all women reported adjusting their dietary and exercise practices with the aim to improve their health and/or PCOS (82% and 73% respectively), however less than 13% reported achievement of health goals (12.2% and 8.1% respectively). Low carbohydrate, high protein diets, and vigorous activity were associated with self-perceived effectiveness (r.0.16, p < 0.01; r.0.15 p < 0.01 and r.0.2 p < 0.01 respectively). Barriers for lifestyle interventions included psychosocial factors. Response bias was not assessed for the Facebook group, however self-reported PCOS aligned with prevalence of clinical phenotypes and suggests results are generalizable to clinical populations of women with PCOS, who are responsible for self-directing and administering lifestyle interventions to manage their PCOS. Conclusions Perceptions of effectiveness for lifestyle interventions by women with PCOS may be complicated by a lack of rigorous evidence. The strength of recommendations in clinical practice guidelines may be enhanced by clinical trials investigating flexible and feasible lifestyle interventions for women in the community with PCOS.